Proteomics in pancreatic disease - Löhr, J.-Matthias; Faißner, Ralf (Pancreatology, 2004)
Proteomics represents a novel methodological approach to investigate the expression of all proteins by a cell or organism in its entireness, similar to global strategies for DNA (genomics) and RNA (transcriptomics). This review focuses on the history of protein analysis, which made up the golden age of pancreatic physiology, the current methodology for proteomics (2D gel electrophoresis, mass spectrometry) and the few published experiences with proteomics in the field of pancreatology until now. Finally, potential applications of proteomics for the pancreas, in concert with other techniques, are cited.